Edukasi Menabung Sejak Dini Guna untuk Memanajemen Keuangan Dimasa Depan Bagi Anak Anak di Mesjid Taqwa Mandala - Filyana Sabhina; Riyan Pradesyah (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2024)
Education about saving from an early age is an important step in forming good financial management skills in children. Educational activities carried out at the Taqwa Mandala Mosque through Real Work Lectures (KKN), aim to increase children's understanding of the importance of saving and simple financial records. The research method used is a qualitative approach with counseling techniques, where children are introduced to the concept of saving using the media "Saving paper and piggy banks." This activity lasted for 15 days, with a focus on direct interaction to facilitate better understanding. The results of this activity show high enthusiasm among children and an increase in their knowledge about financial management. Support from PRM Mandala also plays an important role in the success of the program. Even though there are challenges, such as low interest in saving, this education has succeeded in instilling awareness of the importance of discipline in managing money. It is hoped that this activity can become a model for efforts to develop financial literacy in other communities, as well as have a positive impact in forming healthy financial habits for children.